Big Data's Call to Philosophers of Education - Blanken-Webb, Jane (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
This paper investigates the intersection of big data and philosophy of education by considering big data’s potential for addressing learning via a holistic process of coming-to-know. Learning, in this sense, cannot be reduced to the difference between a pre- and post-test, for example, as it is constituted at least as much by qualities of experience as it is the situation, process of inquiry and its consequences. Long a perennial concern of philosophers of education, the author suggests that big data offers a budding opportunity for philosophers to engage in dialogue with empirical research in order to better understand the process of learning as coming-to-know. Drawing on John Dewey’s theory of inquiry and his philosophy of experience, the author demonstrates ways that both empirical and philosophical research stands to benefit from cross-dialogue. In offering an unprecedented glimpse of empirical detail, the author proposes that big data stands to afford new insights into this most complex human process and that Dewey’s philosophy offers a vital lens of interpretation that can help philosophers of education to make use of this data in addressing the perennial question of how humans come-to-know.